Does Inequality Breed Altruism or Selfishness? Gauging Individuals' Predispositions towards Redistributive Schemes - Fabiana Machado (Inter-American Development Bank (IDB), 2012)
While decreasing inequality is generally considered desirable, and there is a growing understanding of which policies do and do not promote equality, much less is known regarding why these policies are adopted to varying degrees of intensity in different times and places. To explain this variation, the constituencies for different policies under various conditions must be identified. This paper explores that question using Brazilian public opinion data on preferences regarding taxation, conditional cash transfers, pension schemes and educations. It is found that disagreement across socio-economic groups arises on how government should address inequality rather than whether it should do so. While poorer respondents support cash transfers more than the rich, the rich are more likely than the poor to support expenditures on public education. Contrary to what is commonly assumed, inequality seems to breed altruism among the rich regarding the quintessential poverty reduction scheme of conditional cash transfers.
Keywords: H53; I28; I38; 330